BIMBINGAN DAN KONSELING ISLAM DALAM MENINGKATKAN RELIGIUSITAS SISWA SEKOLAH MENENGAH ATAS (SMA) - kuliyatun kuliyatun (INSTITUT AGAMA ISLAM NEGERI METRO, 2020)
The existence of Islamic guidance and counseling services at school can be used as a method by teachers in providing guidance and motivation to students in accordance with the teachings of the Qur'an and Hadith by applying religious values ​​as a guide or foundation for students in overcoming all the problems they face. Lack of religious understanding is one of the factors that lead to deviant behavior towards adolescents, it can occur when individuals do not have a strong religious foundation so they are easily affected by environmental conditions, so there is a need for a process of mentoring learning and religious education. Guidance and counseling in the view of Islam is an effort made to solve a problem that occurs in a person based on Islamic norms. Based on the function of Counseling Guidance in the Islamic view of everything that is done in order to enrich the potential of the students and try as much as possible to find out what is being experienced in order to obtain the right solution and have a life in God's favor both in the world and in yaumil end.